The Potential Vector Competence and Overwintering of West Nile Virus in Vector Aedes Albopictus in China - Zhang, Ying-mei; Guo, Xiao-xia; Jiang, Shu-fang; Li, Chun-xiao; Xing, Dan; Zhang, Heng-duan; Dong, Yan-de; Zhao, Tong-yan (Frontiers in Microbiology, 2022)
West Nile virus (WNV) is an arbovirus, which causes widespread zoonotic disease globally. In China, it was first isolated in Jiashi County, Kashgar Region, Xinjiang in 2011. Determining the vector competence of WNV infection has important implications for the control of disease outbreaks. Four geographical strains of Aedes Albopictus (Ae. Albopictus) in China were allowed to feed on artificial infectious blood meal with WNV to determine the infection and transmission rate. The results indicated that four strains of Ae. Albopictus mosquitoes could infect and transmit WNV to 1- to 3-day-old Leghorn chickens. The infection rates of different strains were ranged from 16.7 to 60.0% and were statistically different (χ2 = 12.81, p < 0.05). The highest infection rate was obtained from the Shanghai strain (60.0%). The transmission rates of Ae. Albopictus Shanghai, Guangzhou, Beijing, and Chengdu strains were 28.6, 15.2, 13.3, and 6.7%, respectively. Furtherly, the results reveal that Ae. Albopictus Beijing strain infected orally can transmit WNV transovarially even the eggs are induced diapausing. The study confirmed that WNV could survive in the diapause eggs of Ae. Albopictus and could be transmitted to progeny after diapause termination. This is of great significance for clarifying that the WNV maintains its natural circulation in harsh environments through inter-epidemic seasons.